PENERAPAN METODE COOPERATIVE SCRIPT UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK CERITA FANTASI PADA SISWA KELAS VII A SMP NEGERI 4 KUTA UTARA TAHUN PELAJARAN 2023/2024 - Artayani, Ni Luh Putri Pramesti; Indrawati, I Gusti Ayu Putu Tuti; Laksmi, Anak Agung Rai (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2024)
This research is Classroom Action Research (PTK) which aims to (1) determine the improvement of students' listening skills using the cooperative script method in class VII A students at SMP Negeri 4 North Kuta for the 2023/2024 academic year; and (2) find out the steps for the cooperative script method to improve listening skills in learning fantasy stories for class VII A students at SMP Negeri 4 North Kuta for the 2023/2024 academic year. The subjects of this research were 29 students in class VII A of SMP Negeri 4 North Kuta. Data collection methods include observation and tests. The data collection instruments used were observation sheets and tests. The learning outcomes of listening to students' fantasy stories increased after the second cycle was carried out. In cycle I, students' learning outcomes in listening to fantasy stories increased with an average score of 5.1 in the almost sufficient category. In cycle II the average score for students' listening to fantasy stories was 8.1 in the good category. It can be said that in the implementation of cycle II, the skill in listening to fantasy stories increased by getting the best score. So it can be concluded that the application of the cooperative script method can improve the fantasy story listening skills of class VII A students at SMP Negeri 4 North Kuta for the 2023/2024 academic year. Abstrak Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang bertujuan untuk (1) mengetahui peningkatan keterampilan menyimak siswa dengan menggunakan metode cooperative script pada siswa kelas VII A SMP Negeri 4 Kuta Utara tahun pelajaran 2023/2024; dan (2) mengetahui langkah-langkah metode cooperative script untuk meningkatkan keterampilan menyimak dalam pembelajaran cerita fantasi pada siswa kelas VII A SMP Negeri 4 Kuta Utara tahun pelajaran 2023/2024. Subjek dari penelitian ini adalah siswa kelas VII A SMP Negeri 4 Kuta Utara sebanyak 29 orang. Metode pengumpulan data berupa observasi dan tes. Instrumen pengumpulan data yang digunakan adalah lembar observasi dan tes. Hasil belajar menyimak cerita fantasi siswa mengalami peningkatan setelah dilakukan II siklus. Pada siklus I hasil belajar menyimak cerita fantasi siswa mengalami peningkatan dengan nilai rata-rata 5,1 kategori hampir cukup. Pada siklus II nilai rata-rata hasil menyimak cerita fantasi siswa 8,1 kategori baik dapat dikatakan bahwa pada pelaksanaan siklus II ini peningkatan keterampilan menyimak cerita fantasi mengalami peningkatan dengan memperoleh nilai paling baik. Maka dapat disimpulkan bahwa penerapan metode cooperative script dapat meningkatkan keterampilan menyimak cerita fantasi pada siswa kelas VII A SMP Negeri 4 Kuta Utara tahun pelajaran 2023/2024.